UNDERSTANDING THE MOTIVES AND TYPIFICATIONS OF YOUTUBER GAMING ON SOCIAL MEDIA: A PHENOMENOLOGY STUDY - Afdal Makkuraga Putra; Andreas Dion Anggoro; Sofia Aunul; Riza Darma Putra (ASPIKOM Jabodetabek Region, 2021)
This study aims to analyze the motives and typify of Youtuber Mobile Legend Bang Bang (MLBB). This study uses Alfred Schutz's theory of phenomenology with a constructivist paradigm and phenomenological methods. To collect data, it was done by interviewing 7 informants and observing the informants' YouTube channel. The results of the research and data analysis show that there are several